Levels of Extracellular Vesicles in Pulmonary and Peripheral Blood Correlate with Stages of Lung Cancer Patients - Choi, Byeong Hyeon; Quan, Yu Hua; Rho, Jiyun; Hong, Sunghoi; Park, Yong; Choi, Yeonho; Park, Ji -Ho; Yong, Hwan Seok; Han, Kook Nam; Choi, Young Ho; Kim, Hyun Koo (World journal of surgery, 2020)
Background The extracellular vesicle (EV) concentration is known to be higher in cancer patients than in healthy individuals. Herein, we report that EV levels differ in the tumor-draining pulmonary vein blood and the peripheral blood of animal models and human subjects at different pathological stages of lung cancer. Methods Ten rabbits and 40 humans formed the study cohorts. Blood was collected from the peripheral vein of members of all groups. Pulmonary blood was collected intraoperatively from all groups except for the healthy human controls. Quantitative analysis of EV levels was performed using a nanoparticle tracking assay, a CD63 enzyme-linked immunosorbent assay, and western blotting. Results The EV levels in the peripheral blood of animals and patients with lung cancer were higher than those in the peripheral blood of healthy controls ( p < 0.01 and p < 0.001, respectively). Moreover, for both animals and patients with lung cancer, the EV levels in the pulmonary blood were significantly higher than those in the preoperative peripheral blood ( p < 0.01 and p < 0.0001, respectively). In patients, the pathological stages of lung cancer showed a higher correlation with the pulmonary EV levels than the peripheral EV levels. Conclusions EV levels increased with increasing lung cancer grade, and this trend was more prominent in the pulmonary blood than in the peripheral blood.